Interfaces e perspectivas históricas do processo de formação continuada de professores do Programa "Teia do saber" no estado de São Paulo: elementos para o debate - Paula, Mauro Lima de (2015)
This dissertation to analyze a Continuing Education Program - FC of teachers, the "Web of Knowledge" in São Paulo nos 2003 and 2005. For the search director, elected how question/problem: What are the interfaces Web of Knowledge program with the Continuing Education Perspective Teachers structured nos Principles" As school locus of Teacher Training "to" Recognition and Measurement of teaching knowledge "and to" Professional Life cycle Teacher"? In this search, we advocate a CF que Teachers consider a school teacher and SUA Practice of the Program Development For Official Organizations TO YOUR Implementation. Thus, we use the theoretical authors defend that Teacher FC Perspective, how Candau (1997), Schon (1992), Nóvoa (1992), Garcia (1992) and Tardif (2002). Therefore, we carried out a qualitative approach to search and use How Data Production and Analysis Instruments the Document Analysis Method (CELLARD, 2008) and Content Analysis (BARDIN, 2011 and FRANCO, 2012). As for the production and data analysis source, we will use Two Official Documents produced For the Ministry of Education of São Paulo - SEESP , a saber , the Educational Policy Document of the Ministry of Education of São Paulo - PESEESP OE Basic Design Document do Web of Knowledge program - PTS . The results indicate that the PTS maintains relationship with the principle of "school how locus", even what superficially and enough with the neoliberal ideas significantly. Regarding the principle of recognition and measurement of teaching knowledge and make professional life cycle of teachers, could not find elements that would give evidence some intreface